Idle-Free Campaign Survey Results and Idling Reductions in an Elementary School - Daniel L. Mendoza; Madelyn Bayles; John R. Contreras; Ryan Bares; Casey S. Olson; Erik T. Crosman; Rachel T. Forrest (Vehicles, 2022)
Air pollution near schools is particularly problematic. Pollution emissions from vehicle idling at or around schools may have significant effects on children’s health including increased rates of asthma and childhood leukemia. Outdoor pollution emissions from idling vehicles can also infiltrate into the schools resulting in health hazards both in school drop-off zones as well as inside nearby buildings. An Idle-Free Campaign was enacted at an elementary school to reduce idling among parents dropping off and picking up students. The campaign involved a focus group, surveys, informational events and materials, and vehicle counting efforts before and after the campaign. The surveys found that regardless of gender or level of education, parents were very concerned about air pollution concerns associated with idling and were willing to take steps to reduce their children’s exposure. Furthermore, the vehicle counting efforts showed a 17% reduction in idling vehicles and a 37% reduction in idling time following the anti-idling campaign. These findings show that a multi-pronged approach involving parents, teachers, staff, bus drivers, and delivery truck drivers, may be an effective tool to reduce idling at schools thus reducing children’s exposure.